2016
DOI: 10.1088/1741-2560/13/4/046009
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neuron-to-EMG decoder training for FES neuroprostheses

Abstract: Objective We have previously demonstrated a brain-machine interface (BMI) neuroprosthetic system that provided continuous control of functional electrical stimulation (FES) and restoration of grasp in a primate model of spinal cord injury (SCI). Predicting intended EMG directly from cortical recordings provides a flexible high-dimensional control signal for FES. However, no peripheral signal such as force or EMG is available for training EMG decoders in paralyzed individuals. Approach Here we present a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Research in the field of brain computer interfaces (BCIs) has consistently demonstrated that brain activity in the intact motor cortex can be leveraged to establish a direct, functional connection to assistive devices that can restore motor and sensory functions 1 4 . More recent work has shown that signals recorded from the brain can be used to directly activate paralyzed muscles via functional electrical stimulation (FES) 5 11 . In humans, BCI control of FES (BCI-FES) has enabled control of hand movements in paralyzed participants 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of brain computer interfaces (BCIs) has consistently demonstrated that brain activity in the intact motor cortex can be leveraged to establish a direct, functional connection to assistive devices that can restore motor and sensory functions 1 4 . More recent work has shown that signals recorded from the brain can be used to directly activate paralyzed muscles via functional electrical stimulation (FES) 5 11 . In humans, BCI control of FES (BCI-FES) has enabled control of hand movements in paralyzed participants 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…For the mean values, 95% confidence intervals were presented, and the hypothesis test for a mean based on the distribution of the t-value was performed to evaluate if the mean response of the individual differs from the applied stimulus. For each electrical stimulus frequency (20,25,30,35,40,45,50,75, and 100 Hz) the null hypothesis was tested for and stated that the mean response of the MMG signal of the individual was equal to the value of the stimulus frequency. In comparison, the alternative hypothesis stated that the mean response is different from the stimulus frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Nine NMES profiles were applied to the neuromuscular tissue to activate the femoral nerve. They consisted of a bipolar rectangular carrier frequency set at 1 kHz (100 ms-on and 900 ms-off), randomly modulated at 20,25,30,35,40,45,50,75, and 100 Hz. The load cell feedback allowed monitoring of force production in which the tension should sustain 5% MVIC during 10 s. An interval of 2 min between each session was allowed for muscle recovery (42).…”
Section: Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative algorisms depend on input signals typically obtained using non-invasive electromyography (EMG) or motion sensors [42][43][44][45][46]. Less common is the use of electroencephalography (EEG) derived signals to control the FES [47,48]. Both EMG and motion sensing inputs can be obtained from the paretic limb or remotely from non-paretic locations.…”
Section: Fes As a Clinical Training Toolmentioning
confidence: 99%